Motivation and attitude in learning English among UiTM students in the northern region / Samsiah Bidin …[et al.] - Bidin, Samsiah; Musa, Aishah; Abdul Aziz, Nurazila; Adzmi, Nor Aslah (Research Management Institute, 2005)
The purpose of this study was to describe the relationship between the students’ motivation and attitudes and their English Language performance, as measured by the UiTM BEL 100 (Preparatory English) English Language examination results. A total of 620 part two students from three UiTM campuses in the Northern Region were taken as the subjects for this study. The research tool used was in the form of a questionnaire. Two variables used in this study which are motivation and attitude were adapted from Gardner and Lambert (1972). A reliability test was conducted on the instrument, and the data analysis yielded a reliability value that was statistically acceptable. The measurement of student’s performance was based on their BEL 100 English examination scores. A correlational research design was used in this study. Analysis of the motivation and achievement data using the descriptive statistics - mean scores revealed that the students were more extrinsically than intrinsically motivated when learning English. However, the one-way ANOVA test showed that there is no significant difference between motivation and English language performance. To test the students’ attitudes and their performance, the Spearman Rho Rank-Order Correlation Coefficient was used and from the analysis, there is a significant correlation between attitude and achievement. The one-way ANOVA was also used and the analysis revealed that there is a significant difference between the students’ attitude in learning English and their English Language performance. The descriptive statistic - mean score was used to find out whether there is any difference between the respondents of different gender and their attitude in learning English. From the results obtained, gender showed the existence of significant differences as related to the English Language performance.